Production of a monoclonal antibody specific for seminomas and dysgerminomas. - Bailey, D (1986)
A monoclonal antibody (M2A, IgG2a) was produced against a cultured human ovarian epithelial adenocarcinoma cell line, HEY. Monoclonal antibody M2A reacted with a glycoprotein of molecular weight 40,000 on the surface of HEY cells. The affinity constant of the monoclonal antibody M2A for HEY cells was 10(9) M-1, and the number of binding sites on HEY cells was 2 X 10(4) per cell. The monoclonal antibody produced positive immunoperoxidase staining of fetal (but not adult) testis and of seminomas and dysgerminomas but did not stain various normal adult tissues or other gonadal or extragonadal tumors. Monoclonal antibody M2A may be useful for confirming a histological diagnosis of seminoma and dysgerminoma.